Innovation in Trás-os-Montes traditional products: consumer perception about new products derived from alheira - Estevinho, Leticia M. (2018)
Innovation is a key factor to generate profitability and growth ensuring that companies succeed and remain in the market even in difficult economic and financial periods (Nielsen, 2015). Companies need to be continually innovating to be competitive. In this context, many companies invest in the development of new products to gain a greater market share and to achieve higher profits. Consumers have a strong appetite for innovation and demand quantity, quality and variety of products. Sociodemographic characteristics have a significant influence on consumer behavior regarding the adoption of new products (Wang, Dou and Zhou, 2008). This work is part of a project developed under ProDeR, measure 4.1 - Cooperation for innovation, dedicated to the development of new products derived from alheira, namely, snacks with alheira filling. The project results from a partnership between a research unit and an industrial company.